(untitled) (Research, Society and Development, 2022)
The treatment of atrophic jaw fracture is a challenge in maxillofacial surgery, due to both local and systemic factors of the affected patients. This article aims to report a case of bilateral atrophic fracture of the mandible treated with an intraoral approach through a thinner and locked 2.0 mm system mandibular plate and subsequent rehabilitation with an implant- supported prosthesis. This technique provided the patient with excellent masticatory, aesthetic, and functional recovery with less morbidity and faster recuperation.